RETRACTION NOTICE â€œA VALUE CHAIN ANALYSIS ON MILKFISH COMMODITY IN SIDOARJO, EAST JAVAâ€ - Anita Nurazyizyah; Budi Setiawan; S Syafrial (Agricultural Socio-Economics Journal, 2021)
This article entitled â€œA VALUE CHAIN ANALYSIS ON MILKFISH COMMODITY IN SIDOARJO, EAST JAVAâ€ (2021), authored by Anita Nurazyizyah, Budi Setiawan, S Syafrial, published in Volume 21, Issue 2. of AGRISE - Agricultural Socio-Economics Journal, pp. 149-154 has been retracted as requested by the authors.